AUGMENTED REALITY-BASED LEARNING: NEEDS ANALYSIS ON ELECTRICITY TOPICS FROM THE PERSPECTIVE OF HIGH SCHOOL STUDENTS - Zeni Haryanto; Shelly Efwinda; Nurhayati Nurhayati; Muhammad Sholeh; Ary Norsaputra (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
One form of educational and technological development is using Augmented Reality as an alternative learning media today. This study aimed to identify the needs of high school students for Augmented Reality-based Learning in Electricity Topics. This research involved 60 high school students in Samarinda. Data was collected using instruments such as observation sheets and questionnaires. The data analysis technique used descriptive qualitative and quantitative. The observation results show that the learning media commonly used are video and virtual simulations through the lecture method. Students are also used to and allowed to use smartphones to access modules and learning materials in class. The results of the questionnaire data analysis show that most students agree that the use of technology is needed to study electricity topics. The majority of students recognize the potential of AR but lack practical experience with it, indicating a significant opportunity for its integration into learning. This research concludes that augmented reality learning is needed as an alternative learning media for electricity. Therefore, we recommend that stakeholders be able to use or develop Augmented Reality media as a source of learning.